2021
DOI: 10.1186/s12865-021-00409-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide- TLR-4 Axis regulates Osteoclastogenesis independent of RANKL/RANK signaling

Abstract: Background Lipopolysaccharide (LPS) is an endotoxin and a vital component of gram-negative bacteria’s outer membrane. During gram-negative bacterial sepsis, LPS regulates osteoclast differentiation and activity, in addition to increasing inflammation. This study aimed to investigate how LPS regulates osteoclast differentiation of RAW 264.7 cells in vitro. Results Herein, we revealed that RAW cells failed to differentiate into mature osteoclasts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 65 publications
(98 reference statements)
4
40
0
Order By: Relevance
“…This is in line with a study which showed that LTA suppressed RANKL-mediated osteoclastogenesis through TLR-2 activation and inhibition of the DNA-binding activity of AP-1 but not NFATc1 (55). Addition of TLR-ligands or bacterial supernatants after pre-priming of macrophages with RANKL accelerates osteoclastogenesis (56)(57)(58) through increased production of pro-inflammatory cytokines such as TNF-α (59,60). Simultaneous activation of TLRs together with RANK, like in our approach, was shown to inhibit osteoclast formation of macrophages (61,62).…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with a study which showed that LTA suppressed RANKL-mediated osteoclastogenesis through TLR-2 activation and inhibition of the DNA-binding activity of AP-1 but not NFATc1 (55). Addition of TLR-ligands or bacterial supernatants after pre-priming of macrophages with RANKL accelerates osteoclastogenesis (56)(57)(58) through increased production of pro-inflammatory cytokines such as TNF-α (59,60). Simultaneous activation of TLRs together with RANK, like in our approach, was shown to inhibit osteoclast formation of macrophages (61,62).…”
Section: Discussionsupporting
confidence: 89%
“…M1 macrophages polarized by LPS in cooperation with IFN-γ do not form TRAP + OCs, but fuse to form multinucleated giant cells (MGCs) [ 158 , 159 ]. M1 macrophages polarized by LPS alone also fail to form OCs in response to RANKL [ 104 ]. However, LPS stimulates OC formation from RANKL-primed pre-OCs indirectly by stimulating TNFα and IL-1β production, although LPS directly inhibits RANKL-induced OC formation [ 105 ].…”
Section: Regulation Of Oc Forming Potential Through Macrophage Polarizationmentioning
confidence: 99%
“…Injection of LPS in animals results in severe bone resorption ( Kim et al, 2021 ). Different to RANKL signaling, LPS-induced activation of osteoclasts is mainly mediated by TLR4 transmembrane protein ( AlQranei et al, 2021 ). Binding with its receptor TLR4, LPS also recruits TRAF6 into cytoplasm and further activates NF-κB signaling pathway ( He et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%